Pengaruh Varian Menu Minuman Terhadap Kepuasan Pelanggan di Naturalis Koffie - Fatimah, R. Naurah; Hidayat, Arif; Ekawati, Rina (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to determine how the effect of beverage menu variations on customer satisfaction. This research uses a questionnaire as a tool in collecting data on 63 respondents. For the analysis technique used is quantitative descriptive analysis. Descriptive analysis is used to determine and be able to explain the characteristics of the variables studied in a situation. The results of this study are based on simple linear regression analysis based on the t value: it is known that the thinag value is 7.223> table 2.453, so it can be concluded that the Trust variable Drink Menu Variations (X) has an effect on the Customer Satisfaction Participation variable (Y).